Isolation and identification of Trichoderma spp. in paddy soils at Machang, Kelantan - Nurul Hazreen Mohamad Kusnin (2016)
Trichoderma is a soil borne mycoparasitic fungus which comprises a number of fungal strains that act as biocontrol agent which effectively against a number of pathogenic fungi. In this study, the paddy soils at Machang, Kelantan was investigated by using the soil dilution plate technique. A total of four Trichoderma spp. isolates were isolated from soil samples obtained from two different sites labelled as Machang A and Machang B. These isolates were identiﬁed and characterized by using the identiﬁcation key techniques which based on the macro- and micromorphological characteristics. The characterization through macromorphology includes examination on the colony appearance, growth rate on Potato Dextrose Agar (PDA), while the shapes and size of conidia, the branching patterns of conidiophores and phialides were observed through micromorphology under the microscope. These isolates of Trichoderma species were identiﬁed and ascribed to two species namely as T. harzianum (TH) and T. koningii (TK). The identiﬁed species were coded as THMPA1 (T. harzianum Machang paddy site A colony 1), THMPA2 (T. harzianum Machang paddy site A colony 2), TKMPA3 (T koningii Machang paddy site A colony 3) and THMPB4 (T. koningii Machang paddy site B colony 4). As the Trichoderma spp. is commonly used as biological control agent against pathogenic fungi, thus, in this study the Trichoderma isolates were also tested as antagonistic activity against Pyricularia oryzae, a pathogen for rice blast disease in paddy. The antagonistic test were carried out by employing dual culture technique to observe the percentage of inhibition on mycelial growth of pathogenic fungi, Pyricularia oryzae by Trichoderma isolates. The outcomes of the dual culture tested found that among the different isolates of Trichoderma, isolate THMPA2 shown the best inhibition with 71.09% antagonistic activity compared to other isolates (69.56% TKMPA3, 69.56% TKMPB4, and 68.04% THMPA1). In all, the species or strain of isolated Trichoderma can be selected as a promising strain of Trichoderma spp. against rice fungal pathogen of Pyricularia oryzae that caused rice blast in rice.